Effect of Write Head Movement On Magnetic Spin Domain Reversal of Nanocube Co/Pd Alloy Material Using Micromagnetic Simulation - Baskoro, Ilham Heru; Lestari, Merinda (Computational And Experimental Research In Materials And Renewable Energy, 2019)
An analysis of the effect of the write head movement on the reversal time of the domain spin with magnetic Co/Pd on the magnetic recording layer has been carried out through micromagnetic simulation. The magnetic recording layer is modeled in the form of cubes (nanocubes) which consists of 5 domain spin. The write head, which is a transduser, moves along the domain spin to write data in the form of magnetic spins, which represent the bits on the magnetic recorder perpendicular. The results of this simulation are a profile of changes in the total magnetic field and reversal time of the domain spin when writing magnetic data for 6 nanoseconds. The calculation used in this study is an analytical calculation regarding the reversal time of the magnetic domain spin of the Co/Pd alloy material. The formulation for calculating the reversal time of domain-spin magnetization is a combination of graphical analysis and analytical calculations with visualization of the magnetic spin configuration that consisting of 5 domains spin. This simulation was carried out using the finite element method and obtained a saturation 5 field value of the magnetic alloy Co/Pd (Hs) material of 2.5 x 105 A/m and a write head (Hwh) field that 6 must be applied to the magnetic recording layer in order to reverse the uniform domain spin is 7.3 x 106 A/m. Each size of the domain spin requires a different write head, the smaller the nanocube size, the greater the write head field applied to the magnetic recording layer. Meanwhile, the effective write head 6 field amplitude that is suitable for the 20 nm domain spin is 8.3 x 106 A/m. A significant change in the total field occurs when the domain spin reverses 3 times in the first domain spin (n1), the third domain spin (n3) and the fifth domain spin (n5). The total field value when t=0.42 ns ( first domain spin reversal) is 73.69376 A/m, then the total field at t=0.42 ns (third domain spin reversal) is 3443.197 A/m and the current total field t=0.42 ns (fifth domain spin reversal) of 5480.696 A/m.